Responsive web design with HTML5 and CSS develop future-proof responsive websites using the latest HTML5 and CSS techniques - Frain, Ben (Expert insight., 2020)
Harness the latest capabilities of HTML5 and CSS to create a single UI that works flawlessly on mobile phones, tablets, and desktops -- plus everything in-between Key Features Understand what responsive web design is and its significance for modern web development Explore the latest developments in responsive web design including variable fonts, CSS Scroll Snap, and more Get to grips with the uses and benefits of the new CSS Grid layout Book Description Responsive Web Design with HTML5 and CSS, Third Edition is a renewed and extended version of one of the most comprehensive and bestselling books on the latest HTML5 and CSS tools and techniques for responsive web design. Written in the author's signature friendly and informal style, this edition covers all the newest developments and improvements in responsive web design including better user accessibility, variable fonts and font loading, CSS Scroll Snap, and much, much more. With a new chapter dedicated to CSS Grid, you will understand how it differs from the Flexbox layout mechanism and when you should use one over the other. Furthermore, you will acquire practical knowledge of SVG, writing accessible HTML markup, creating stunning aesthetics and effects with CSS, applying transitions, transformations, and animations, integrating media queries, and more. The book concludes by exploring some exclusive tips and approaches for front-end development from the author. By the end of this book, you will not only have a comprehensive understanding of responsive web design and what is possible with the latest HTML5 and CSS, but also the knowledge of how to best implement each technique. What you will learn Integrate CSS media queries into your designs; apply different styles to different devices Load different sets of images depending upon screen size or resolution Leverage the speed, semantics, and clean markup of accessible HTML patterns Implement SVGs into your designs to provide resolution-independent images Apply the latest features of CSS like custom properties, variable fonts, and CSS Grid Add validation and interface elements like date and color pickers to HTML forms Understand the multitude of ways to enhance interface elements with filters, shadows, animations, and more Who this book is for Are you a full-stack developer who needs to gem up on their front-end skills? Perhaps you work on the front-end and you need a definitive overview of all modern HTML and CSS has to offer? Maybe you have done a little website building but you need a deep understanding of responsive web designs and how to achieve them? This is a book for you! All you need to take advantage of this book is a working understanding of HTML and CSS. No JavaScript knowledge is needed.